THE PURE THEORY OF LAW AND THE EXCLUSION OF SOCIOLOGY - Aristizábal, José Fredy (2019)
Hans Kelsen considers in his work “Pure theory of law” that legal science must be separated from other sciences. Kelsen’s reason consists in his consideration that sociology has been trapped by rationalist empiricism, and his motivation is that Law can not be reduced to an auxiliary science of sociology, which leads him to construct a statute of his own. legal science, rationalist type.